Power performance, flow behaviour and excitation response of canted blades for a vertical axis wind turbine - Armstrong, Shawn (My University, 2011)
The ability of vertical axis wind turbines to operate effectively in the presence of highly unstable, turbulent wind flow patterns makes them ideal candidates for small scale applications in urban environments, where enatic wind flow patterns are quite common. Their axisymmetric nature allows for wind energy extraction during conditions of rapidly varying wind direction, and their base mounted generator location permits relatively easy maintenance, making them a more suitable design for small scale urban installations as compared with traditional horizontal axis turbines. Wind tunnel experiments were canied out on a small scale, high solidity, three-bladed Danieus wind turbine with canted (tilted) blades. The effects of preset blade pitch (β =+2.5°, -1.5°, -3.5° and -5.5°) and of aerodynamic fences were investigated at high Reynolds numbers (>500,000) for their effect on power performance while simultaneously characterizing the flow behaviour on a section of the inner blade surface using Mylar tufts and a shaft-mounted video camera. The excitation response of the turbine was also measured. The results are compared to a set of similar straight blades.
The results of pitching the canted blades show that the power performance increases up to CPmax =0.28 for increasing outward blade pitch, to a best observed pitch of β = -3.5° after which the power performance decreases. Canted blades show acute sensitivity to inwards pitch where the power coefficient dropped to CPmax =0.06 at β =
+2.5°. The power coefficient observed for canted blades was CPmax = 0.29 at 9 m/s wind speed which was slightly higher than CPmax = 0.26 measured for the equivalent set of straight blades that were tested at the same preset pitch (β = -3.5°) at 10 m/s wind speed. The maximum power coefficient occurred at a higher blade speed ratio for canted blades ( λ =2.15) compared to straight blades (λ = 1.7) despite nearly identical solidities (σ = 0.45 for canted blades versus σ =0.43 for straight blades). Aerodynamic fences improve the power performance of canted blades to CPmax =0.29 at 8 mls wind speed to and CPmax =0.31 at 10 mls wind speed and reduce the speed at which peak power occurs to λ =1.9. Aerodynamic fences do not noticeably change the power performance of straight blades.
Flow visualization using Mylar tufts attached to the inside blade surface indicated that canted blades experience reversed flow exclusively during the upwind pass of their rotation at peak power. Overall, canted blades experience less reversed flow than straight blades at the same blade speed ratio and only develop minor reversed flow during the downwind pass for blade speed ratios substantially below peak power where straight blades experience significantly more reversed flow. Aerodynamic fences further reduce the amount of reversed flow on canted blades, especially directly below the fence.
Due to differences in the peak operating speeds and the primary natural frequencies of the wind turbine with canted blades and straight blades, a direct comparison of the excitation response of canted blades and straight blades is not presently possible. However, normalizing the data suggests that canted blades do show reduced excitation response over straight blades.
This study shows that the Current set of canted blades produces acceptable power levels, with the potential for further refinements to improve performance, and suggests that reduced excitation response can be achieved with canted blades.
Keywords: Mechanical Engineering; Mechanical Engineering